10058-F4 Mediated inhibition of the biofilm formation in multidrug-resistant Staphylococcus aureus - Hiren Dodia; Suvendu Ojha; Puja Chatterjee; Tushar Kant Beuria (Biofilm, 2025)
Antimicrobial resistance (AMR) is a global concern that undermines microbial disease treatment and prevention. WHO and World Bank's EcoAMR report predicts that AMR could cause 39 million deaths and $3.4 trillion in annual GDP losses by the year 2050. This is particularly critical with S. aureus, a cause of diverse infections like skin abscesses and pneumonia, where antibiotic resistance increases mortality and hinders treatment. Biofilms are one of the major causes of multi-drug resistance in S. aureus, and their inhibition can restore antibiotic sensitivity. In this study, through screening of the LOPAC drug library, we identified several compounds that exhibit biofilm inhibitory properties against multi-drug-resistant S. aureus without affecting its growth. The compound 10058-F4 was found to have the strongest anti-biofilm activity (>70 % inhibition) with minimal antibacterial effects (MIC 256 μg/mL); however, it showed no inhibitory effects on pre-existing biofilm. Further, the 10058-F4 treatment suppressed the expression of sarA, the biofilm master regulator, along with biofilm genes, such as icaA, fnb, nuc, and sspA. Additionally, the results showed that 10058-F4 synergistically enhanced the antibacterial activity of norfloxacin and tetracycline, indicating its potential use as an adjunct to the existing antibiotic treatments. While these findings suggest the potential of 10058-F4 for clinical use, further investigations are necessary to elucidate its mechanism of action and optimize its application in combination therapies.